Fabrication of Customized Nanogel Carriers From a UV-Triggered Dynamic Self-Assembly Strategy - Bao, Wuren; Lyu, Jieran; Li, Chunlin; Zhang, Jifeng; Sun, Tunan; Wang, Xing; Zhou, Jin; Li, Dawei (Frontiers in Chemistry, 2019)
Recent advances in self-assembled nanogel carriers have enabled precise fabrication of hierarchical architectures using a low-cost solution-phase protocol. Typically, photochemical strategy on the tailor of morphology and dimension has emerged as a powerful tool, because light-trigger has exceptional advantages of an instant ‘on/off’ function and spatiotemporal precision at arbitrary time. Herein, we report a tunable manipulation of sequential morphology and size transition in situ via a ‘living’ thiol-disulfide exchange reaction from a UV-tailored hierarchical self-assembly strategy. By varying the irradiation time, the photochemical method can easily fabricate and guide series of attractively architectural evolution in aqueous solutions, by which the improving hydrophobicity and sensitive redox-responsiveness endowed these disulfide-linked nanoparticles with remarkable capacities of abundant encapsulation, effective separation and controlled release of hydrophobic cargoes. Notably, once the thiol-disulfide exchange is interrupted at any moment by removing the UV lamp, the active sites of nanogel carriers are deactivated, and thus no further morphology evolution is conducted any more. However, these stable inert sites can be reactivated whenever needed, and the trapped morphology evolution can get back on their right track, which may provide a simple and novel approach to fabricating the desired self-assemblies in aqueous solutions. With regard to this advanced functionality, various nanogel carriers with customizable structures and properties have been customizable yielded and screened for cancer therapy. Thus, this ‘living’ controlled self-assembled method to program morphology and size evolution in situ is a universal strategy that will pave a novel pathway for creating the sequential shape-shifting and size-growing nanostructures and constructing uniform nanoscopic functional entities for advanced biological applications.